1996
DOI: 10.1111/j.1532-950x.1996.tb01423.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Autologous Tendon Graft Repair Method for Gap Healing of the Deep Digital Flexor Tendon in Horses

Abstract: A sutured tenorrhaphy technique that incorporated an autologous tendon graft was compared mechanically and histologically with a sutured tenorrhaphy at 6, 12, and 24 weeks after repair. Tenorrhaphy was performed in the forelimb tendon of the deep digital flexor muscle and the graft was taken from the hindlimb tendon of the lateral digital extensor muscle; one forelimb site included the graft, whereas the other forelimb site was not grafted. Tenotomies were made immediately proximal to the insertion of the acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
2
5

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 14 publications
2
32
2
5
Order By: Relevance
“…As rupturas do tendão músculo gastrocnêmio podem ocasionar alteração postural grave de difícil correção (VAUGHAN, 1980). Na perda expressiva de parte do tecido tendíneo, a substituição torna-se necessária por meio de enxerto ou com o emprego de próteses, que fornecem suporte e orientação para a migração de células e formação de fibras (VALDÉS-VAZQUEZ;McCLURE;OLIVER, 1996). Entretanto, apesar de serem disponíveis vários métodos de tratamento de lesões tendíneas, ainda é necessário o desenvolvimento e aprimoramento de métodos que permitam o retorno morfológico e funcional do tendão (GOODSHIP, 1993).…”
Section: Introductionunclassified
“…As rupturas do tendão músculo gastrocnêmio podem ocasionar alteração postural grave de difícil correção (VAUGHAN, 1980). Na perda expressiva de parte do tecido tendíneo, a substituição torna-se necessária por meio de enxerto ou com o emprego de próteses, que fornecem suporte e orientação para a migração de células e formação de fibras (VALDÉS-VAZQUEZ;McCLURE;OLIVER, 1996). Entretanto, apesar de serem disponíveis vários métodos de tratamento de lesões tendíneas, ainda é necessário o desenvolvimento e aprimoramento de métodos que permitam o retorno morfológico e funcional do tendão (GOODSHIP, 1993).…”
Section: Introductionunclassified
“…A secção do tendão calcâneo comum ou dos flexores digitais leva a alteração postural grave que poderá ser de difícil correção, não sendo incomum nas espécies canina (Vaughan, 1980;Bonneau et al, 1983), eqüina (Goodship, 1993) e humana (Nystrom & Holmlund, 1983). A substituição do tendão torna-se necessária especialmente quando há perda de parte do tecido e, nesses casos, o enxerto ou a prótese fornecem suporte e orientação para a migração de células e formação de fibras (Valdés-Vásquez et al, 1996). Ocasionalmente tendões devem ser alongados ou encurtados devido a defeito de conformação, desenvolvimento inadequado ou por complicações de tratamentos de feridas que envolvem essas estruturas (Clark, 1993).…”
Section: Introductionunclassified
“…The repaired tendons during the early stages of healing must be protected from full weight bearing through some form of external cooptation, regardless of the method and material used to reconstruct the damaged tendon until the collagenous scar has developed adequate tensile strength to support weight bearing function (Lin et al 2004;Dehghani & Varzandian 2007). Valdez-Vazquez et al (1996) found that in vitro data for healing of SDFT revealed load failure ranged from less than 150 kg at 6th week to 600 kg at 9-12th weeks and up to 700 kg at 24th week. However, load failure of the DDFT at 6th week is slightly more than 100 kg, by 12th week it is about 260 kg and by 24th week, it is 575 kg.…”
Section: Biomechanical Properties Of the Digital Flexor Tendonsmentioning
confidence: 99%
“…The use of allografts appeared as successful as that of autograft, but if fresh allografts are used a donor animal is required each time (Valdez-Vazquez et al 1996;Soliman et al 1999). The efficacy of carbon fibres and plasma preserved tendon allograft for gap repair in the SDFT in 12 crossbred calves.…”
Section: Digital Flexors Tenorrhaphy With Allograftmentioning
confidence: 99%
See 1 more Smart Citation